Evaluation of some pepper genotypes as rootstocks in water stress conditions - Penella, Consuelo; Nebauer, Sergio G.; López-Galarza, Salvador; San Bautista, Alberto; Rodríguez-Burruezo, Adrian; Calatayud, Ángeles (2017)
Water stress is a major environmental factor that limits crop production and it is important to develop crop varieties with higher yield under water scarcity. Increased pepper tolerance to water stress through grafting onto robust rootstocks could be an optimal alternative in the context of environmentally friendly agriculture. Our work evaluated the behaviour of 18 pepper genotypes during vegetative and reproductive stages under water stress in order to select tolerant genotypes to be used as rootstocks for pepper cultivation. The pepper tolerance screening was based on photosynthetic parameters. The genotypes Atlante, C-40, Serrano, PI-152225, ECU-973, BOL-58 and NuMex Conquistador were revealed as the most tolerant genotypes to water stress because they maintained net photosynthetic rate levels under water stress conditions. The selected genotypes were validated as rootstocks on a pepper cultivar in terms of productivity under severe water stress. Plants grafted onto cvs Atlante, PI-152225 and ECU-973 showed higher marketable yields when compared with ungrafted cultivar.